ZLY032, the first-in-class dual FFA1/PPARδ agonist, improves glucolipid metabolism and alleviates hepatic fibrosis. (September 2020) - Li, Zheng; Zhou, Zongtao; Hu, Lijun; Deng, Liming; Ren, Qiang; Zhang, Luyong
Graphical abstract: Chronic treatment with ZLY032, the first-in-class dual FFA1/PPARδ agonist, revealed greater benefits on glucolipid metabolism and fatty liver than TAK-875, the most advanced candidate of FFA1 agonists. Moreover, ZLY032 prevented CCl4 -induced liver fibrosis by reducing the expressions of genes involved in inflammation and fibrosis development. Highlights: ZLY032 improved glucolipid metabolism and fatty liver in ob/ob mice and NASH model. ZLY032 exhibited better insulin sensitivity and lipid improvement than TAK-875. ZLY032 improved pancreatic β-cell function of ob/ob mice. ZLY032 prevented MCD diet-induced or CCl4 -induced liver fibrosis. ZLY032 regulates genes related to lipid metabolism, inflammation, fibrosis, oxidative stress and mitochondrial function. Abstract: The free fatty acid receptor 1 (FFA1) and peroxisome proliferator-activated receptor δ (PPARδ) are considered as anti-diabetic targets based on their role in improving insulin secretion and resistance. Based on their synergetic mechanisms, we have previously identified the first-in-class dual FFA1/PPARδ agonist ZLY032. After long-term treatment, ZLY032 significantly improved glucolipid metabolism and alleviated fatty liver in ob/ob mice and methionine choline-deficient diet-fed db/db mice, mainly by regulating triglyceride metabolism, fatty acid β-oxidation, lipid synthesis, inflammation, oxidative stress and mitochondrial function. Notably, ZLY032 exhibited greater advantages on lipid metabolism, insulin sensitivity and pancreatic β-cell function than TAK-875, the most advanced candidate of FFA1 agonists. Moreover, ZLY032 prevented CCl4 -induced liver fibrosis by reducing the expressions of genes involved in inflammation and fibrosis development. These results suggest that the dual FFA1/PPARδ agonists such as ZLY032 may be useful for the treatment of metabolic disorders.